2017
DOI: 10.1534/genetics.117.300207
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalins Are Required for Apical Extracellular Matrix Organization and Remodeling in Caenorhabditis elegans

Abstract: A lipid and glycoprotein-rich apical extracellular matrix (aECM) or glycocalyx lines exposed membranes in the body, and is particularly important to protect narrow tube integrity. Lipocalins ("fat cups") are small, secreted, cup-shaped proteins that bind and transport lipophilic cargo and are often found in luminal or aECM compartments such as mammalian plasma, urine, or tear film. Although some lipocalins can bind known aECM lipids and/or matrix metalloproteinases, it is not known if and how lipocalins affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(89 citation statements)
references
References 86 publications
(119 reference statements)
10
79
0
Order By: Relevance
“…Other sheath proteins also have been observed within the vulva (Forman-Rubinsky et al, 2017;Gill et al, 2016), and the adult vulva becomes cuticle-lined in adults (Page & Johnstone, 2007;Sulston & Horvitz, 1977). These observations suggested to us that a sheath-like matrix may exist within the developing vulva lumen.…”
Section: Background: Vulva Tube Formationmentioning
confidence: 57%
See 3 more Smart Citations
“…Other sheath proteins also have been observed within the vulva (Forman-Rubinsky et al, 2017;Gill et al, 2016), and the adult vulva becomes cuticle-lined in adults (Page & Johnstone, 2007;Sulston & Horvitz, 1977). These observations suggested to us that a sheath-like matrix may exist within the developing vulva lumen.…”
Section: Background: Vulva Tube Formationmentioning
confidence: 57%
“…Each fusion protein initially appeared at around the L4.2 stage, and then exhibited a temporally and spatially distinct pattern over the course of L4 vulva morphogenesis ( Figure 3B-D). All six matrix proteins were transient and disappeared by the time that animals reached the adult stage, indicating that they are not components of the mature cuticle, but rather define a distinct matrix type present only during morphogenesis (Forman-Rubinsky et al, 2017;Gill et al, 2016) (and data not shown).…”
Section: Sheath Aecm Proteins Show Dynamic Patterns Of Localization Dmentioning
confidence: 91%
See 2 more Smart Citations
“…We have established C. elegans as an in vivo model to study the interplay between TGF-β signaling and ECM. The C. elegans ECM includes both basement membrane, which lines internal organs, and cuticle, which is secreted apically from hypodermal tissue to protect the organism and is shed at each molt [3][4][5]. The cuticle is composed of multiple collagen layers coated by a lipid-rich epicuticle [6,7].…”
Section: Introductionmentioning
confidence: 99%